Modern Information Technologies in the System of Financial and Economic Security of the Enterprise (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article presents the interpretation of financial and economic security and characterized the approaches to its assessment at the enterprise. The publication proves that using computer information systems at the enterprise is needed to strengthen its information security, as an integral component of financial security, in order to avoid unauthorized access to confidential information resources. Since in the modern information space entities increasingly use modern ERP-systems to automate not only the accounting and analytical process, but also all economic activity. The establishment of information security in such conditions requires special attention. Thus, to effectively ensure financial and economic security at the enterprise, it is necessary to develop and successfully implement an appropriate mechanism, which should include: instruments, methods and levers for the formation of the financial security of the enterprise and an information-analytical component of such security functioning on the basis of modern information technologies.
Keywords: the modern information technologies, financial and economic security, information system of the enterprise, information security